2020
DOI: 10.36419/jkebin.v11i1.332
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pemberian Asi Eksklusif Terhadap Status Gizi Balita

Abstract: Latar Belakang : Terjadinya masalah gizi pada bayi disebabkan antara lain oleh karena ASI banyak digantikan oleh susu formula dengan jumlah dan cara yang tidak sesuai dengan kebutuhan bayi. Menurut WHO, setiap tahunnya terdapat 1-1,5 juta bayi yang meninggal akibat tidak diberikannya ASI Ekslusif. Kematian balita dapat dicegah dengan diberikannya ASI Ekslusif. Bayi yang diberi ASI Ekslusif selama enam bulan dapat menurunkan angka kematian balita sebesar 13%. Tujuan : Mengetahui hubungan pemberian A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Exclusive breastfeeding with the nutritional status of toddlers in this study showed a Okta et al : Factor Related To Incident Of Malnutrition… Indonesian Midwifery and Health Sciences Journal, 2024, 8(1), 73-83 79 statistically influential relationship with a p-value of 0.024. In addition, Hanifah (2020) in her research also stated that the majority of toddlers who get exclusive breastfeeding from their mothers have normal nutritional status, with a p-value of 0.000. These results show that there is significance between exclusive breastfeeding and the nutritional status of toddlers.…”
Section: Complementary Feeding Infectious Diseases Exclusive Breastfe...mentioning
confidence: 95%
“…Exclusive breastfeeding with the nutritional status of toddlers in this study showed a Okta et al : Factor Related To Incident Of Malnutrition… Indonesian Midwifery and Health Sciences Journal, 2024, 8(1), 73-83 79 statistically influential relationship with a p-value of 0.024. In addition, Hanifah (2020) in her research also stated that the majority of toddlers who get exclusive breastfeeding from their mothers have normal nutritional status, with a p-value of 0.000. These results show that there is significance between exclusive breastfeeding and the nutritional status of toddlers.…”
Section: Complementary Feeding Infectious Diseases Exclusive Breastfe...mentioning
confidence: 95%
“…ASI eksklusif adalah pemberian ASI tanpa makanan tambahan lain pada bayi berumur 0 -6 bulan. Bayi tidak diberikan apa -apa, kecuali makanan yang langsung diproduksi oleh ibu karena bayi memperoleh nutrisi terbaiknya melalui ASI (Hanifah & Sab'ngatun, 2020. Pada penelitian Ikro, dkk (2021, diketahui bahwa riwayat pemberian…”
Section: Riwayat Pemberian Asi Eksklusifunclassified
“…Stunting adalah masalah kurang gizi kronis yang disebabkan oleh asupan gizi yang kurang dalam waktu cukup lama akibat pemberian makanan yang tidak sesuai dengan kebutuhan gizi. (Hanifah, 2020).…”
Section: Pendahuluan 11 Latar Belakangunclassified